The Flexibility of Connubium Relationship Among Minangkabau Matrilineal Clans: A Study of Pariaman Rantau Communities in Kota Bekasi - Fachruliansyah, Iman; Sayfa'at, Riyan Habie; Febrian (Universitas Airlangga, 2025)
This study explores how Minangkabau perantauan (migrant) communities in Bekasi, West Java, reinterpret the traditional circulating connubium, a system of marital alliances between matrilineal clans, through adaptive practices such as the Bajapuik dowry tradition and intra-group clans’ marriage. Using a focused ethnographic approach, we conducted a series of preliminary, informant identification, and data collection through observation and in-depth interviews with members of the Pariaman community. While classical structural anthropology models frame the Minangkabau kinship through ideally exogamous marriage rules, we document how urban migrants strategically modify these norms to sustain matrilineal identity. Ethnographic data reveal that prohibited unions (e.g., Koto-Piliang marriages) and flexible Bajapuik payments reflect what we call the flexibility of connubium: a dynamic process wherein adat (custom) persists through selective adaptation rather than cultural erosion. Theoretically, we extend Sahlins’ (2013) notion of “mutuality of being” to argue that these practices embed migrants into shared existential projects, transcending geographic displacement. Our findings challenge the assumptions that urbanization erodes tradition, showing instead how kinship evolves through sasamo awak (“among our own”) alliances that prioritize clan solidarity over classical exogamy.